Role of Phosphogypsum and Ceramic Dust in Amending the Early Strength Development of a Lime Stabilized Expansive Soil - James, Jijo; Pandian, P. Kasinatha (International Journal of Sustainable Construction Engineering and Technology, 2017)
This investigation delves into the potential of two solid wastes viz. Phosphogypsum (PG) and Ceramic Dust (CD) in enhancing the development of the early strength of an expansive soil. The minimum lime content required for modification of the soil called as Lime Modification Optimum (LMO) was determined using pH test. The expansive soil was then stabilized using one lime content chosen below LMO and another lime content chosen above LMO. These two lime contents were amended with varying doses of the two solid wastes. The unconfined compressive strength of the stabilized soil combinations with and without additives was determined after curing for three different periods of 2 hours, 3 days and 7 days. The results of the strength tests were analyzed and compared for the two solid wastes adopted as additives. The results showed that PG enabled a quicker development of strength of the lime stabilized soil whereas CD did not have much of an influence on the early strength of the stabilized soil.